Factors Influence the Intention to Communicate in English Among Clerical Staff at Universiti Utara Malaysia - Nooraini @ Noorfizani, Hussein (2011)
This final project paper studies about factors to influence the intention to communicate in English among clerical staff at University Utara Malaysia. The objective of study to determine whether there is a relationship between attitude and training effectiveness with the intention to communicate in English language among supporting staff. The questionnaire was developed and distributed to the sample. This study was conducted on a sample of 158 supporting staff of UUM. The result was found that there is a significant relationship between attitude with the intention to communicate in English and training effectiveness with the intention to communicate in English among supporting staff of UUM.